An Assessment of the Need to Establish a Nursing Training Institution in Narok County, Kenya - Otulo P; Ngotiek P; Yiaile AL; Serrem CK; Menge D; Wanzala W (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Background: Nursing profession is focused on caring individuals, families and communities with a view to helping them attain, maintain, or recover optimal health and quality of life in the society. Nurses are therefore on high demand in order to meet the defi cit and adequately combat health problems in the society. Objective: The objective of this study was therefore to evaluate the need to establish a training institution for nurses in Narok County in order to increase the nursing workforce. Materials and Methods: A baseline study was conducted by administering a well-structured questionnaire to key respondents who comprised health workers, particularly health managers within Narok County and its environs. A comprehensive literature review was conducted and contrastingly and analytically compared. Data analysis utilized descriptive statistics using SPSS version 22. Results: Out of 30 respondents, over 70% were married while less than 30% were single. In terms of gender, 80% of the respondents were female while the remaining 20% were male. Most respondents (85%) had only training in tertiary institutions compared with those who had attained university level qualifi cations (15%). 77% of the respondents were aware of the situation of nursing profession in the County while 23% were not. 76.9% of the respondents had a positive attitude towards nursing profession while 23.1% indicated that they did not have a positive attitude towards nursing profession. Those who had positive attitude indicated they can keep dignifi ed attitude towards nursing profession. On advancement of their careers, 90% of those interviewed indicated they were ready to continue in advancing their  nursing education. Many respondents (85%) indicated that the practice of nursing is admirable in Narok County. Some respondents reported staff shortage, promotion problems, less motivation, people's attitudes and lack of facilities to be among the major challenges facing the nursing profession. Conclusion: In conclusion, as much as there is need to address major issues related to promotion, job security, health resources, establishment of appropriate nursing cadre in nursing industry and understaffing, the establishment of a training institution to increase the nursing workforce in Narok County  is exceptional.